LEOPARD syndrome and hypertrophic obstructive cardiomyopathy: a case report - Çetinkaya, Ergun; Günal, Nazlıhan; Sönmez, Nilgün; Aycan, Zehra; Vidinlisan, Sadi; Kahramanyol, Öz; Paşaoğlu, İlhan (The Turkish Journal of Pediatrics, 2004)
The LEOPARD syndrome is a rare, autosomal dominant multisystemic disorder characterized by lentiginosis, ocular hypertelorism, abnormal genitalia, growth retardation, sensorineural deafness, and cardiac and electrocardiographic abnormalities. Although it is not cited, hypertrophic cardiomyopathy is often associated with the disease. In this study, we present a nine-year-old boy with LEOPARD syndrome and hypertrophic obstructive cardiomyopathy.